SECM/SKP and SVET studies on mitigation of N80 steel corrosion by some polymers. (11th June 2018) - Feng, Hongwei; Singh, Ambrish; Wu, Yuanpeng; Lin, Yuanhua
Abstract : Three polymers, namely PAMPS (P1), P(AMPS- co -NVP) (P2) and P(AMPS- co -DMC) (P3), synthesized by common solution polymerization were investigated as corrosion inhibitors for N80 steel in 3.5 wt% NaCl flooded with CO2 . Abstract : Three polymers, namely PAMPS (P1), P(AMPS- co -NVP) (P2) and P(AMPS- co -DMC) (P3), synthesized by common solution polymerization (CSP) were investigated as corrosion inhibitors for N80 steel in 3.5 wt% NaCl flooded with CO2 by high temperature high pressure (HPHT) weight loss, electrochemical methods (EIS, Tafel), scanning electrochemical microscopy (SECM), scanning Kelvin probe (SKP), scanning vibrating electrode (SVET) techniques, and surface studies (UV-Visible, SEM). The P1 inhibitor exhibited the best inhibition efficiency among the polymers at 500 ppm concentration. The adsorption of the polymer derivatives obeyed the Langmuir isotherm. SECM measurements revealed a difference in the current on the steel surface with and without polymers. SKP and SVET showed the potential difference between the cathodic and anodic regions of the metal surface with and without inhibitors.